Structural and functional insights into γ-glutamyl carboxylase-factor IX interaction: implications for vitamin K-dependent bleeding disorders - Kang Liu; Shixin Li; Guomin Shen; Jiangbo Tong; Nan Jiang; Minwen Hong; Yi Gu; Luju Chen; Yuan Zhao; Jinlin Huang; Jian-Ke Tie; Zhenyu Hao (Haematologica)
Not available.